Tradisi Ngedeblag di Desa Kemenuh: Refleksi Komunikasi Komunal Dalam Kehidupan Modern - A.A. Putra Dwipayana; I Gede Sutana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This paper describes comprehensive the communication that is communal in the form of community interaction in the ngedeblag tradition carried out by the people of Kemenuh Village as part of respect for tradition and maintaining the balance of the energy of the universe. The presence of modern life, does not necessarily only affect the life of urban communities which tend to be heterogeneous. However, through cultural and market expansion, massive economic growth, and social mobility, a civilization that can generalize all aspects of life can even form the individualistic and materialistic side of each individual. Uniquely, the presence of a tradition in the life of people in Bali can become a fortress for this form of generalization. As seen in Kemenuh society, it is related to the ngedeblag tradition which is believed to be part of a ritual to drive out evil spirits or negative forces, and to restore the balance of the great bhuwana. In ongoing observations, the tradition of ngedeblag is actually a reflection of the life of the communal community. This is indicated by the process of interaction through community communication patterns that occur from the beginning of preparation for the implementation of the ngedeblag tradition to the end of the tradition. Not only in the aspect of social interaction, the communication of this tradition also has implications for the next generations of the existence of the ngedeblag tradition as part of cultural heritage and understanding the expression or intent to be conveyed through the ngedebalag tradition.Keywords: Ngedeblag Tradition, Communal Communication, Modern Life